Is this atherosclerosis in patients with HIV? Data received by OCT. (14th October 2021) - Efendieva, N M; Shevchenko, O P; Sozykine, A V; Nikitin, A E; Shevchenko, A O; Orlova-Morozova, E A; Vasilyeva, V P; Shlykov, A V; Novikova, N A
Abstract: Background: Chronic infection by HIV evolves with a vascular inflammatory action causing endothelial dysfunction. The action of the virus as well as the side effects of antiretroviral drugs contributes to the progression of cardiovascular diseases. The study aimed to characterise the changes of the structure of the coronary wall and the thickening of the intima by Optical Coherence Tomography in HIV-infected patients with or without symptoms of coronary heart disease. Methods: Fifty-two HIV-infected individuals had a mean age of 49.8±11.4 years. There were 75% men, diabetes 30, 8%, hypertension 30, 8%, smokers 34, 62% and 7, 7% with cholesterol levels ≥99 mg/dl. Control group included 120 non-HIV-infected controls with coronary heart disease. All the participants from HIV-group receive ART, 100% of participants had plasma HIV RNA <20 copies/mL and 78, 85% of them have symptoms of coronary artery disease. Results: The average diffuse homogeneous thickening of the intima in patients with HIV was 0.67±0.24 mm, and 0.34±0.18 mm in control group, with normal values not exceeding 0.05 mm. There was impaired three-layer structure of coronary wall in 90, 4% (47 of 52) HIV-infected participants and in 60% of control group, atherosclerotic plaque had only 34, 62% of HIV group. All HIV-infected patients receive ART more than 5 years. Conclusion: The coronary angiography and OCT demonstratedthat the inflammatory process resulting from HIV-infection or HAART may be relevant in the changes of coronary arteries in HIV-positive patients. The changes are predominantly represented by thickening of the intima, impaired three-layer structure of arterial wall and accelerating atherosclerosis. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Russian National Research Medical University named after N.I. PirogovCentral Clinical Hospital of Russian Academy of Science, Moscow, Russia